Impact of personal and environmental factors affecting exclusive breastfeeding practices in the first six months during the COVID-19 pandemic in Thailand: a mixed-methods approach - Sasitara Nuampa; Ameporn Ratinthorn; Crystal L. Patil; Kornkanok Kuesakul; Sudhathai Prasong; Metpapha Sudphet (BMC, 2022)
Abstract Background Exclusive breastfeeding (EBF) for six months is recommended as one of the most important ways to support child health and survival, particularly during the COVID-19 pandemic. However, breastfeeding women encountered several obstacles during the pandemic. The purpose of this study was to conduct a survey to document breastfeeding practices, EBF rates and associated factors with six month exclusive breastfeeding during the second wave of the coronavirus outbreak in Thailand. Methods A mixed-methods design that included a cross-sectional survey (n = 390) and semi-structured in-depth interviews (n = 15) was carried out between August and November 2021. Participants were women aged ≥ 15 years who had given birth within 6-12 months before data collection and delivered in three public hospitals in the top three provinces with the most severe COVID-19 outbreaks. Results The median duration of EBF was four months (interquartile range, IQR: 1-6 months) and 37.4% of women exclusively breastfed for six months. From binary logistic regression models, several personal factors were associated with exclusive breastfeeding for six months including being a housewife (AOR 2.848; 95% CI 1.512, 5.367), perceived sufficiency of family income (AOR 2.502; 95% CI 1.362, 4.594), working from home/business (AOR 2.071; 95% CI 1.074, 3.995), breastfeeding intention (AOR 1.162; 95% CI 1.116, 1.210), and maternal age (AOR 0.932; 95% CI 0.882, 0.986). From qualitative interviews, women who were able to exclusively breastfed during the outbreak explained five themes that were a protective shield; I have to save money, I could spend all my time with my baby and breastfeed, spousal support is valuable, and opportunity to avoid the obstructed beliefs about exclusive breastfeeding. Conclusions Mothers with higher socioeconomic status and who were unemployed/worked from home and had support structures in place were able to successfully EBF during the COVID-19 outbreak. Healthcare providers can better support breastfeeding if they provide informational support and allow family members to participate in breastfeeding programs, especially spouses who provided key emotional and tangible support during pandemic.